DIAGNOSIS OF SICK SINUS SYNDROME: CLINICAL AND ELECTROCARDIOGRAPHIC EVALUATION - Passos, Mauro de Deus; de Macedo, Ryan Rafael Barros; Bergamo, Fernando Malachias de Andrade; Barbosa, José Micael Delgado; da Silva, Ivaldo Arnaldo Olimpio; Zimmer, Luiz Gustavo Cambruzzi; Pinheiro, Alex Ramon Nunes; dos Santos, José Ricardo; Costa, Fernando Gomes; Alves, Claudeban Bento; Rodrigues, Caio; Santos, Rubia Martinez (Editora Impacto Científico, 2025)
Sinus Node Syndrome (SNS), or Sinus Node Dysfunction, is a disorder of cardiac automaticity and conduction prevalent in the elderly, characterized by sinus bradycardia, pauses, and chronotropic incompetence. This narrative review analyzes current diagnostic strategies, highlighting the importance of correlating clinical symptoms of hypoperfusion (syncope, dizziness) and electrocardiographic findings. The etiology is multifactorial, encompassing irreversible intrinsic causes, such as degenerative fibrosis, and reversible extrinsic causes, including the use of drugs (e.g., Remdesivir) and metabolic disorders. Diagnosis is challenging due to the intermittency of symptoms and may require prolonged monitoring (Holter) to detect occult arrhythmias. The study also addresses tachycardia-bradycardia syndrome and the need to differentiate SNS from neurological conditions that mimic its symptoms.DOI: https://doi.org/10.56238/edimpacto2025.091-032